2014
DOI: 10.1183/09031936.00118114
|View full text |Cite
|
Sign up to set email alerts
|

Selection criteria for intensive care unit referral of lung cancer patients: a pilot study

Abstract: The decision-making process for the intensity of care delivered to patients with lung cancer and organ failure is poorly understood, and does not always involve intensivists. Our objective was to describe the potential suitability for intensive care unit (ICU) referral of lung cancer in-patients with organ failures.We prospectively included consecutive lung cancer patients with failure of at least one organ admitted to the teaching hospital in Grenoble, France, between December 2010 and October 2012.Of 140 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
1
12
0
3
Order By: Relevance
“…For example, a recent cohort of 49, 515 metastatic patients with acute coronary syndrome documented a percutaneous coronary intervention (PCI) for only 24.9% of ST elevation myocardial infarction (STEMI) and 9.6% for non‐STEMI . In addition, while both short term and long term prognosis of cancer patients admitted to intensive care units has considerably improved, many patients are not considered as candidates for intensive care, or admitted after a detrimental delay . We are unaware of reports of less dramatic interventions, but it is likely that cancer patients are undertreated by physicians who consider them to have a very poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent cohort of 49, 515 metastatic patients with acute coronary syndrome documented a percutaneous coronary intervention (PCI) for only 24.9% of ST elevation myocardial infarction (STEMI) and 9.6% for non‐STEMI . In addition, while both short term and long term prognosis of cancer patients admitted to intensive care units has considerably improved, many patients are not considered as candidates for intensive care, or admitted after a detrimental delay . We are unaware of reports of less dramatic interventions, but it is likely that cancer patients are undertreated by physicians who consider them to have a very poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Such an awareness might have direct practical implications; physicians who have a pessimistic view of the prognosis of cancer patients might prefer palliative care over investigation and treatment of medical conditions which might influence both quality of life and survival. Cancer patients might receive insufficient therapy during acute hospital admissions and might not be admitted to intensive care units, if the treating physicians believe they have dismal prognosis anyway. A perception of dismal prognosis, sometimes referred to as “therapeutic nihilism”, might turn into one through misconception .…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to consider that the prognosis of lung cancer patients surviving to the ICU stay is relatively poor, with a 6-month mortality rate of 73%, and only two-thirds of those receiving further anticancer treatment survive [8]. In this issue of the European Respiratory Journal, the article by TOFFART et al [9] reflects this situation, with hospital mortality of ∼60% for patients admitted to ICU and a 1-year survival after discharge from the ICU of 12%. Using a population similar to common descriptions, the authors asked how the decisions for referral of lung cancer patients to ICU were taken.…”
mentioning
confidence: 99%
“…but also subjective constraints of a philosophical, psychological or religious nature in their decision. TOFFART et al [9] reported on 140 consecutive lung cancer patients with at least one organ dysfunction admitted to a single general hospital during a 23-month period. What is the main information provided by that prospective pilot study?…”
mentioning
confidence: 99%
See 1 more Smart Citation